Sport Practice and Social Inclusion: A Systematic Review - EL FERDIOUI , Ayoub; SOSSI ALAOUI , Fatimzahra; ZOUKENI , Brahim (Revue Internationale des Sciences de Gestion, 2026)
Sport is increasingly regarded as a potential vehicle for social inclusion in a global context marked by rising inequalities and the reemergence of social tensions. It was a systematic review that adheres to the PRISMA protocol and analyses the works of the last ten years (2015-2025) and in the discipline of sport and the social sciences. A total of eighteen studies focusing specifically on the relationship between sport participation and social inclusion were identified. The results indicate that sport can support the inclusion of marginalized groups such as disadvantaged youth, persons with disabilities and migrants by fostering social networks, participation and a sense of belonging. However, the effectiveness of sport as an inclusion mechanism is strongly shaped by structural, cultural and political conditions, and not all sport-based initiatives generate sustainable outcomes. Critical evaluations also demonstrate the enduring limitations whereby, standardization of research designs that incorporate methodological diversity and the measurement of long-term impact is a nagging issue. All in all, the review highlights the necessity to build purposefully inclusive programs, reinforce the development of stakeholders as well as the encouragement of longitudinal and context-related studies. Sport holds promise as a tool for social integration, but only when its practices are deliberately adapted and subject to rigorous evaluation.